Brothers of Coweta : kinship, empire, and revolution in the eighteenth-century Muscogee world - Rindfleisch, Bryan C. (University of South Carolina Press, 2021)
"[Examines] how family and clan fundamentally structured the Creek world, and ... how a particular family and clan emerged out of the historical shadows to become central players in the Creek world and shaped the forces of empire, colonialism, and revolution that transformed the South during the eighteenth-century. The manuscript pieces together the story of a specific Creek Indian family in eighteenth-century America, and their experiences at the crossroads of the British, French, and Spanish empires in the American South. ... for the most part, scholars of early America and Native America have been unable (and in some cases unwilling) to fully appreciate the kinship, clan, and familial dynamics of Indigenous groups in North America ... However, European authorities, imperial agents, merchants, and a host of other individuals left a surprising paper trail when it came to two Creek personalities: Escotchaby and Sempoyaffee of Coweta, brothers. By following that trail and drawing upon the broader literature related to the Creek Indians in the eighteenth-century, Rindfleisch seeks to recover the intensely intimate and familial dimensions of the Creek world ... The central importance of family and clan in the eighteenth-century Creek world has yet to be fully explored or articulated by scholars of early America and Native America. Instead, historians have demonstrated how one's loyalties to a talwa or community like Coweta, regional identities like Upper Creeks and Lower Creeks, or even national aspirations of a Creek Nation or Confederacy proved foundational throughout a Creek person's life. And while scholars concede that 'family was...a critical component of eighteenth-century Creek local life, particularly for structuring political relations within a community,' there is little that historians understand about the importance of family and clan within the Creek world ... Yet the central premise of the book is to suggest that we can in fact understand and read more into the ways in which family and clan directed the Creek world, as much as - if not more than - talwa, region, and nation"--